Cetuximab activity in dysplastic lesions of the upper aerodigestive tract. (February 2016) - Khan, Zubair; Epstein, Joel B.; Marur, Shanthi; Gillespie, M. Boyd; Feldman, Lawrence; Tsai, Hua-Ling; Zhang, Zhe; Wang, Hao; Sciubba, James; Ferris, Robert; Grandis, Jennifer R.; Gibson, Michael; et al.
Highlights: Clinical trial to determine effects of cetuximab on high risk oral premalignancy. Patients with mild, moderate, severe head and neck dysplasia enrolled. Primary objective to determine histologic response to treatment with cetuximab. Cetuximab may result in histological resolution in at least a subset of patients. Summary: Background: High risk head and neck mucosal premalignancy has a malignant conversion rate of up to 40%, despite adequate surgical therapy. Epidermal Growth Factor Receptor (EGFR) blocking agents, including cetuximab, have shown activity in head and neck squamous cell carcinoma (HNSCC) and have potential for therapy in high risk premalignancy. Methods: We conducted a randomized, prospective, phase II clinical trial to determine the effects of cetuximab on patients with high risk premalignancy. Patients were randomized to treatment with cetuximab 400 mg/m 2 on week one followed by 250 mg/m 2 on week 2–8 or observation, with the option for crossover to cetuximab therapy for patients originally randomized to the observation arm. Results: Two of 19 enrolled patients did not complete therapy due to treatment toxicity. Analysis of 17 patients who completed the trial regimen show a trend toward a larger mean decrease in grade of dysplasia in the cetuximab treated group (−1.0) vs. the observation group (−0.2) ( P = 0.082, one-sided exact Wilcoxon rank sum test). However, in the observation group, none of the 5 patients (0%) achieved complete resolution of dysplasia; while 4 of 12 (33.3%) cetuximab treated patients had no remaining dysplasia after therapy. Conclusions: Treatment of high risk premalignancy of the upper aerodigestive tract with cetuximab alone may result in significant, durable, and complete clinical and histological resolution of moderate to severe dysplasia in at least a subset of high risk patients. These results warrant further investigation in larger studies with increased statistical power.